Response of common beans (Phaseolus vulgaris L.) to seed treatment in Central Kenya - Waswa, Boaz Shaban; Kamau, Eliezah; Karanja, David; Mairura, Franklin S. (Academic Journals, 2022)
Seed treatment presents an opportunity to boost bean productivity; however, the technology has not been widely tested in Kenya and the sub Saharan Africa region. An experiment was carried out at Kandara, Central Kenya to compare the effects of seed treatment applications on bean performance. The split-plot design experiment with three replicates included four seed treatment products: Apron Star, Seed Plus, Gro Plus and TriCoat applied at recommended and half recommended rates with two bean varieties as test crop. Split-plot ANOVA was implemented using Genstat and agricolae R procedures to compare the effects of seed treatment applications on aphid pest severity and bean performance parameters. Varietal performance differences to the seed treatment were observed with Nyota variety performing better than KATB1. Generally, Apron Star at recommended rates reported lowest pest incidences and consistent bean performance over the two cropping seasons. Consistent treatment effects were observed for recommended rates compared to half rate applications. Under favorable environmental conditions, use of the seed treatment products alone produced yields comparable to the fertilizer treatment. The benefits observed from use of seed treatment technology makes it a potentially sustainable strategy for improving productivity for cash strapped small-scale producers in the region.